Analysis of the EDGE Rating System Implementation in PKN STAN Buildings - Tiffany Nurul Aini; Surya Gunanta Tarigan (Architectural Research Journal, 2023)
Indonesia, especially Jakarta and big cities, has now started to promote the development and renewal of green buildings. The green building concept is a concept that is really needed at this time, considering the degradation of environmental quality due to development that does not pay attention to environmental sustainability. The green building concept will certainly encourage every development to be sustainable one. EDGE is an assessment tool that focuses on energy savings and the use of new and renewable energy sources. In order to achieve EDGE standards, buildings must demonstrate a 20% reduction in projected energy consumption, water reduction, and embodied energy in materials compared to conventional buildings. This research uses a case study exploration method regarding the fulfilment of green building criteria in the PKN STAN Building project, based on the EDGE assessment system. Integrating green building certification, especially EDGE, is expected to be a solution to the problems facing the world of construction today.